The Changes of Amygdala Transcriptome in Autism Rat Model After Arginine Vasopressin Treatment - Zhou, Bo; Zheng, Xiaoli; Chen, Yunhua; Yan, Xuehui; Peng, Jinggang; Liu, Yibu; Zhang, Yi; Tang, Lei; Wen, Min (Frontiers in Neuroscience, 2022)
Background: Some studies have shown that AVP can significantly improve the social interaction disorder of autism, but the mechanism remains unclear. Methods: Female Wistar rats were intraperitoneally injected with VPA or Normal Saline at E12.5 to establish an autism model or normal control in their offspring. Male offspring prenatally exposed to VPA were randomly assigned to two groups: The VPA-induced autism model group and AVP group. AVP group were treated with intranasal AVP at PND21 and for 3 weeks. The VPA-induced autism model group were given the same dose of normal saline in the same way. Behavioral responses were evaluated in open field and three-chambered social test apparatus, the expression levels of AVP in Serum was detected by ELISA Assay Kit and the gene expression levels on the amygdala were measured by RNA-Seq at PND42. Results: Intranasal of AVP can significantly improve the social interaction disorder and elevated the levels of AVP in serum. Transcriptome sequencing results showed that 518 differently expressed genes were identified in VPA-induced autism model group compare to control in this study. GO biological process enrichment analysis of DEGs showed that the VPA-induced autism model group had significant nervous system developmental impairments compared with the normal group, particularly in gliogenesis, glial cell differentiation and oligodendrocyte differentiation. GSEA enrichment analysis also showed the biological process of oligodendrocyte differentiation, axoneme assembly, axon ensheathment were inhibited in VPA-induced autism model group. Pathway enrichment analysis of DEGs between control and VPA-induced autism model group showed that the PI3K/AKT and Wnt pathway were significantly dysregulate in VPA-induced autism model group. Few differentially expressed genes was find when compare the transcriptome between the VPA-induced autism model group and AVP treatment group. GSEA enrichment analysis showed deficits in oligodendrocytes development and function were significantly improve after AVP treatment, the pathways were mainly enrichment in NOTCH, MAPK, Focal adhesion signaling pathway, not PI3K/AKT and Wnt pathway. The expression patterns analysis also showed the same results.